2012
DOI: 10.1111/j.1468-1331.2012.03824.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of NR4A2 gene in a large population of Han Chinese patients with Parkinson's disease

Abstract: Collectively, our results suggest that NR4A2 may be a susceptibility gene for PD in the Chinese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 11 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…NURR1 (also known as NR4A2) encodes a member of the steroid-thyroid hormone-retinoid receptor superfamily [ 144 ]. Mutations in this gene have been associated with disorders related to dopaminergic dysfunction including PD [ 145 163 ]. GPR161 0 0 No association between GPR161 and PD was found.…”
Section: Resultsmentioning
confidence: 99%
“…NURR1 (also known as NR4A2) encodes a member of the steroid-thyroid hormone-retinoid receptor superfamily [ 144 ]. Mutations in this gene have been associated with disorders related to dopaminergic dysfunction including PD [ 145 163 ]. GPR161 0 0 No association between GPR161 and PD was found.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, as Milani et al suggested, mutations in NR4A2 could confer more severe clinical manifestations (Milani et al ). NR4A2 has been reported as a possible candidate gene for schizophrenia and Parkinson disorder, because some of its variants have been identified in affected patients, although the extent of the genotype–phenotype association is not particularly strong (Chen et al ; Chen et al ; Liu et al ). Furthermore, a patient exhibiting ID (IQ = 61) but no autistic features has been described, and he had a balanced chromosomal translocation between chr2 and chr17 that resulted in GPD2 disruption (Daoud et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al (2002) and Zheng, Heydari, and Simon (2003) reported associations between homozygosity or heterozygosity for a variant in the intron of this gene and PD. Many follow‐up studies (Le et al, 2003; Liu et al, 2013; Tan et al, 2004) revealed the presence of NR4A2 variants in both familial and sporadic cases of PD among various populations. Our study provided more evidence for the association between rare variants of NR4A2 and sporadic PD in Chinese population.…”
Section: Discussionmentioning
confidence: 99%